Incorporating Spirituality and Market: Islamic Sharia Business and Religious Life in Post-New Order Indonesia - Utama, Wildan Sena (UI Scholars Hub, 2015)
This article examines the religious transformation of the Muslim middle class and its relationship with the growing sharia market in post-New Order Indonesia. It argues that in the Indonesian neo-liberal era, this spiritual revival considerably influenced the economic realm. The transformation of piety of the Indonesian middle class marked the emergence of new potential economic markets. It was responded to enthusiastically by markets producing selective products with a spiritual content. In its process, the role of spiritual lifestyle agents played a pivotal role in helping and shaping the new urban middle class who consume Islam to mark their Islamic identity. It was then that the energetic blending between Islamic piety and capitalism occurred in contemporary Indonesia. Islamic symbolic consumption becomes a new source of spiritualism as well as a source of religious identification. However, this article argues that this process tends to oversimplify Islam as a ‘material process’ rather than a ‘spiritual process’.